The effect of paternal and maternal factors on the prognosis of live birth in couples with recurrent pregnancy loss - Pirkko‐Liisa Peuranpää; Mika Gissler; Paula Peltopuro; Aila Tiitinen; Hanna Hautamäki (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Currently, recurrent pregnancy loss (RPL) examinations focus on the woman, although paternal factors are also involved. Men in couples with RPL have higher sperm DNA fragmentation levels than fertile men, but the effect of sperm DNA damage on couple's later prognosis is unknown. Advanced maternal age and obesity are associated with RPL, but paternal lifestyle factors are less studied. Therefore, we aimed to study the associations of couples' lifestyle factors, causes of RPL, and sperm DNA fragmentation with their prognosis of future live birth. Material and methods This descriptive cohort study comprised 506 couples investigated for RPL at Helsinki University Hospital, Finland, between 2007 and 2016, linked with national health and population registers. The primary outcome was couple's live birth after RPL investigations. Data on couple's background factors, including age, body mass index, smoking, and alcohol use, were collected from medical records. Sperm DNA fragmentation index was analyzed from 211 men using the sperm chromatin dispersion test. The associations between background factors, sperm DNA fragmentation, and cumulative probability of live birth over time were analyzed using cross‐tabulations and age‐adjusted Cox regression. Results In all, 352 of 506 couples (69.6%) achieved live birth. Maternal age, unexplained RPL, prolonged pregnancy attempts before investigations, paternal obesity, and maternal smoking were associated with prognosis: unadjusted hazard ratio for couple's live birth for women aged 35–39 vs younger than 30 years was 0.63 (95% confidence interval [CI] 0.47–0.84), and for 40 years or older was 0.36 (95% CI 0.22–0.58). Age‐adjusted hazard ratio for unexplained vs explained RPL was 1.39 (95% CI 1.12–1.72), for couple's pregnancy attempt at least 4 years vs less than 2 years was 0.50 (95% CI 0.33–0.76), for paternal body mass index at least 30 kg/m2 vs less than 25 kg/m2 was 0.67 (95% CI 0.46–0.98), and for maternal smoking was 0.71 (95% CI 0.51–0.99). Altogether, 96/135 (71.1%) couples with normal (<15%), 38/60 (63.3%) with intermediate (15–30%), and 11/16 (68.8%) with high sperm DNA fragmentation index achieved live birth (p = 0.56). Conclusions In couples with RPL, prolonged pregnancy attempts, a cause found in RPL examinations, lifestyle factors, and maternal age are negatively associated with their prognosis of future live birth. Sperm DNA fragmentation was not associated, but the number of men with damaged spermatozoa was small. We suggest that clinicians include women and men in RPL counseling because couple's joint lifestyle seems to determine their later prognosis.